MORPHOLOGICAL AND ECOLOGICAL FEATURES OF APHID ACYRTHOSIPHON PISUM (HARRIS, 1776) (using the example of Northern Fergana) (Scientific journal of the Fergana State University, 2025)
The article presents the results of a study on “The features of morphoecological adaptation of phytophages to their habitat and food resources.” Using mathematical and statistical methods and on the basis of morphometric features of Acyrthosiphon pisum samples, which is the main pest of chickpeas, the variability of the diversity of individuals in the regions was determined. The geographical and ecotopic variability of phytophages in desert, rainforest and foothill areas was statistically analyzed, and it was also proved that the aphid Acyrthosiphon pisum significantly differs in 9 morphometric features, in accordance with Studenta criteria (tst=2.9; tf>tst or R>0.01).